The Effectiveness of Psychological Well-Being Training based on the PERMA Model for 14 to 16-Year-Old Girls with Anxiety Symptoms - zahra danesian; Shahriar Shahidi; Saeed Ghanbari (پژوهشنامه روانشناسی مثبت)

(untitled)
Well-being combines good feeling and effective performance, which means flourishing. It is achieved by successfully pursuing PERMA's five components: positive emotions, engagement, relationships, meaning, and achievement. Adolescents often experience emotional problems such as anxiety and stress that can negatively impact their psychological well-being and life satisfaction. To address this issue, a research study was conducted to train psychological well-being based on the PERMA model to 14-16-year-old girls with anxiety symptoms. The study used a non-random sampling of accessible and purposeful type by considering 9th and 10th-grade female students (1st and 2nd high school) of Tehran as the statistical population. The research was a quasi-experimental type of group with a pre and post-test and follow-up test design. The training course consisted of 6 weekly sessions of one and a half hours each. The findings showed that after the training course, there was a significant increase in the total score of PERMA and its components, such as positive emotion, engagement, positive relationships, and meaning. Moreover, there was a significant decrease in anxiety symptoms among adolescents. In the three-month follow-up, these positive changes in positive emotion, engagement, and positive relationships were permanent, and engagement increased significantly over time. Despite the improvement in achievement, the changes did not reach a significant level. Based on these findings, it can be concluded that PERMA model training increases flourishing and reduces anxiety symptoms in 14 to 16-year-old girls.IntroductionAdolescence is a critical period marked by significant psychological and social changes. Teenagers today face numerous challenges, including environmental issues and mental health concerns (Morrish et al., 2018). They often experience emotional problems such as anxiety and stress that can negatively impact their psychological well-being and life satisfaction. Effective interventions are needed to support their well-being and academic performance. Positive psychology focuses on fostering positive emotions and traits to enhance mental health. Seligman's PERMA model outlines five pillars of well-being: positive emotions, engagement, relationships, meaning, and achievement. Each pillar contributes to overall happiness and fulfillment, emphasizing the importance of personal strengths and resilience (Seligman, 2011). MethodsThe study employed a quasi-experimental design with pre-test, post-test, and follow-up phases, targeting 9th and 10th-grade female students in Tehran. Based on Jabari et al. (2013), the sample size was calculated to be 15 participants using G*Power software, considering a significance level of 5% and power of 80%. Non-random sampling was conducted among female students aged 14-16 with anxiety symptoms identified via a self-assessment questionnaire (Achenbach Youth Self-Report (YSR)). The PERMA questionnaire, developed by Rashid and Seligman (2013), assesses well-being across five subscales through 25 items scored on a Likert scale. Participants completed the pre-test of the Perma questionnaire before attending six weekly training sessions based on the Perma model. Post-tests and a follow-up questionnaire were conducted three months later. Data analysis utilized SPSS 26, employing descriptive statistics and non-parametric tests, including Friedman's test for comparison among pre-test, post-test, and follow-up scores, and the Wilcoxon test when significant differences were found. A significance level of 5% was applied. ResultsThe average age of 15 participants was 15.2 ±0.86. When comparing pre-test, post-test, and follow-up scores, the results showed that scores generally increased post-test (p < 0.05), except for positive emotion and meaning, which saw slight decreases. Anxiety scores among adolescent girls also decreased, confirming the effectiveness of the PERMA model training on biology grades and anxiety (p = 0.04). Friedman's test revealed significant improvements in biological quality scores (p < 0.05) and components like positive emotions, fascination, participation, and positive relationships among girls aged 14-16. However, meaning and achievement showed no significant change. The Wilcoxon test indicated significant differences between pre-test and post-test scores in positive emotion (p = 0.005), engagement (p = 0.018), positive relationships (p = 0.008), and meaning (p = 0.04). The overall PERMA score also demonstrated significant improvement (p = 0.001). However, achievement scores showed no significant change (p = 0.15). The comparison of anxiety indices before and after the training showed significance (p = 0.04), highlighting the training's effect. Post-test and follow-up results indicated a significant increase in the engagement component (p = 0.002). However, no significant differences were found for positive emotion, positive relationships, meaning, or achievement. The follow-up test showed a notable increase in engagement. Participants noted that exercises related to positive emotions, such as gratitude and reflecting on positive experiences, were the most frequently used (22%). Conclusion The present study explores the impact of training psychological well-being using the PERMA model on adolescent girls aged 14 to 16 who are grappling with anxiety symptoms. Through statistical analysis, the findings reveal a significant increase (p = 0.001) in the participants' PERMA scores following the training, which aligns closely with previous studies conducted by Honarmandzadeh et al. (2016) and others. The program's emphasis on recognizing and nurturing individual strengths through positivity education has profoundly enriched the flourishing components among these female students, showcasing the transformative power of such interventions. The results provide compelling evidence of significant enhancements across multiple dimensions of well-being. Specifically, there were notable increases in positive emotions (p = 0.005), engagement, relationships (p = 0.008), and the search for meaning in life. The study underscores that while positive emotions may be fleeting, they serve as vital catalysts for personal growth and strengthen social connections. Engagement is characterized by a genuine interest and deep investment in activities, while positive relationships are essential for enhancing overall life satisfaction and fostering gratitude. In terms of the achievement component, the results indicated improvement, although they did not reach a statistically significant level. This limitation likely stems from the course duration not being adequate to facilitate observable academic successes, traditionally measured by awards or high grades. However, it is significant to note that students reported an increased sense of happiness derived from recognizing and celebrating small daily successes, illustrating the importance of incremental progress. Teenagers’ self-assessments indicate a significant reduction in anxiety symptoms post-test (p = 0.04), supporting positive psychology's assertion that boosting positive emotions decreases emotional issues (Rashid & Seligman, 2014). Conversely, Tejada-Gallardo et al. (2020) found no significant effects from school-based interventions. While 9 participants reported decreased anxiety, 4 experienced increases, likely due to final exams coinciding with the post-test.In conclusion, this study effectively establishes that the positive training program is a highly impactful approach to enhancing the well-being of adolescents, offering valuable insights into the development of future training interventions aimed at fostering mental health and resilience among young individuals. The present study faces several limitations, including time constraints related to the execution of end-of-semester exams and challenges in practical implementation. Additionally, the absence of a comparison group should be taken into account in future research. Ethical ConsiderationIn conducting this research, informed consent was obtained from participants and their parents. Confidentiality was maintained in the results of the questionnaire. This study received ethical approval under the code IR.SBU.REC.1402.039 from the Martyr Paradise University Ethics Committee.Authors’ ContributionsAll authors contributed to the study. The first author conducted the training for participants and wrote the first draft of the manuscript. The second and third authors edited the manuscript.Conflict of InterestAccording to the authors, this article has no financial sponsor or conflict of interest.FundingThis research received no external funding.AcknowledgmentI would like to express my sincere gratitude to all the experts, students, parents, and teachers who contributed to this research, as well as my colleagues who supported me throughout the process. Corresponding author